TEACHING METHOD: SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) TO IMPROVE STUDENTS’ READING COMPREHENSION - Euis Yanah Mulyanah; Ishak Ishak (Universitas Muhammadiyah Tangerang, 2023)
The research was conducted to observe the effect of the SQ3R on the tenth-grade student’s reading comprehension at SMA Muhammadiyah 2 Tangerang. The research used a quantitative approach and the design of this research was quasi-experiment research by using a non-equivalent control group design by using Random Sampling, consisting of X IPS 1 as an experiment class and X IPS 2 as a control class. The posttest results were obtained data that tcount = 1.29 and ttable = 1.9965 with significant level = 5% or 0.05. This means that H0 = was rejected and H1 was accepted. It is reasonable to suppose that there is a substantial difference in students' reading comprehension between the experiment class taught using the SQ3R technique and the control class not taught using the SQ3R method. Therefore, the SQ3R method can be an alternate approach to improving students’ reading comprehension.